Effects of Formula-100 therapeutic milk and Bregas Nutriroll ready-to-use therapeutic food on Indonesian children with severe acute malnutrition: A randomized controlled trial study - Lubis, Anwar; Riyadi, Hadi; Khomsan, Ali; Rimbawan, Rimbawan; Shagti, Indhira (Narra J, 2024)
Severe acute malnutrition (SAM) is a global health concern that affects children and leads to delayed growth. The aim of this study was to compare the impact of F100 milk and Bregas Nutriroll, a local ready-to-use therapeutic food (RUTF), on SAM children. An unmasked, non-blinded, two-group, and simple randomized controlled trial was conducted. Indonesian children aged 12–59 months with SAM were randomly assigned to receive either F100 milk or Bregas Nutriroll. After eight weeks, the increase in the mean weight gain in both groups was assessed. The Bregas Nutriroll group (n=19) had a mean weight gain of 1.07±0.09 kg, while the F100 group (n=17) had a mean weight gain of 1.05±0.11 kg. The Bregas Nutriroll group had a slightly higher gain of mid-upper arm circumference (MUAC) than the F100 group (0.62±0.34 cm vs 0.50±0.37 cm). The gain of children’s height of the Bregas Nutriroll group was 0.96±0.42 cm, while the F100 group was shorter at a mean of 0.81±0.44 cm. Statistically significant differences (p<0.001) in nutritional status were observed based on weight, MUAC, and height/length after F100 and Bregas Nutriroll interventions. The intervention with F100 increased hemoglobin (Hb) levels of 0.71±1.25 mg/dL, while the Bregas Nutriroll intervention led to an increase of 0.11±1.39 mg/dL. In conclusion, our study showed that community-based treatment with F100 milk or Bregas Nutriroll resulted in nutritional status in children with SAM. These findings suggested that both treatments could be effective in treating SAM in improving nutritional status and child health outcomes.